Customer satisfaction as a mediator between electronic services quality and customer engagement of XXX Private University customers in Yogyakarta - Wafa, Zaenal; Sundjoto, Sundjoto; Rahayu, Sri; Puspitasari, Fanny; Puspitasari, Etin (Universitas Ahmad Dahlan, 2025)
One of the primary concerns in the ongoing economic recession is the decline in the enrolment of students continuing their studies on campus. Consequently, various strategies are necessary to increase the quantity and the extent of customer engagement, in this case, students, thereby fostering their resilience within universities. This study aims to examine the role of service quality in customer engagement, with or without the mediating effect of customer satisfaction. This research employs a cross-sectional study design. The participants in this study are active students at XXX University in Yogyakarta. Data collection instruments include customer engagement, service quality, and customer satisfaction questionnaires. Path analysis is used, specifically Partial Least Squares Structural Equation Modeling (PLS-SEM), facilitated by SmartPLS 3.0. The results of the path analysis in this study indicate that the quality of electronic services plays a significant role in customer engagement through customer satisfaction. This finding is evidenced by a path coefficient of 0.526, which is considered relatively strong (p = 0.000, < 0.01). Additionally, the quality of electronic services has a direct and significant impact on customer engagement, as demonstrated by a path coefficient of 0.159, which is regarded as relatively weak (p = 0.015, < 0.05). This study concludes that customer satisfaction effectively mediates the relationship between electronic service quality and customer engagement.